The Influence of Good Corporate Governance, Firm Size, and Operating Capacity on Financial Distress (Study of Retail Trade Sub-Sector Companies Listed on The Indonesian Stock Exchange in 2017-2022) - Nurhadimah, Siti; Paramita, V. Santi Paramita (Ilomata International Journal of Tax and Accounting, 2024)
Financial distress is a situation that arises when a company has an unstable financial situation. If this condition continues, it will impact the company’s bankruptcy. This research aims to determine the influence of Good Corporate Governance, Firm Size, and Operating Capacity on Financial Distress in the retail trade sub-sector listed on the Indonesia Stock Exchange in 2017-2022. The independent variables of Good Corporate Governance include the audit committee, board of commissioners, board of directors, managerial ownership, and institutional ownership. The research method uses a quantitative and associative approach. The population in this study was 27 companies with a sampling technique using purposive sampling, and 25 companies were obtained as samples, so 150 observation data were obtained. The data analysis technique in this research uses logistic regression analysis using IBM SPSS 25 software. The partial research results show that the audit committee, managerial ownership, institutional ownership, and firm size do not affect financial distress. The board of commissioners, board of directors, and operating capacity negatively affect financial distress. Simultaneously, Good Corporate Governance, Firm Size, and Operating Capacity influence financial distress. This research implies that companies must pay attention to the good corporate governance sub-variables related to the board of commissioners and board of directors because these sub-variables have been proven to influence financial distress. Apart from that, companies must also pay attention to their operating capacity because, in this research, this variable was proven to influence financial distress.